2011
DOI: 10.1115/1.4003719
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Unsteady Tip and Endwall Heat Transfer in a Highly Loaded Transonic Turbine Stage

Abstract: In a previous study, vane-rotor shock interactions and heat transfer on the rotor blade of a highly loaded transonic turbine stage were simulated. The geometry consists of a high pressure turbine vane and a downstream rotor blade. This study focuses on the physics of flow and heat transfer in the rotor tip, casing, and hub regions. The simulation was performed using the unsteady Reynolds-averaged Navier–Stokes code MSU-TURBO. A low Reynolds number k-ε model was utilized to model turbulence. The rotor blade in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Referring to Yang et al [31] and Shyam et al [33], the results with TwaU corresponding to 70% of the inlet temperature are cal culated and selected for discussion. With the purpose of preventing from shock wave as mentioned above, the flow fields in all domains are subsonic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Referring to Yang et al [31] and Shyam et al [33], the results with TwaU corresponding to 70% of the inlet temperature are cal culated and selected for discussion. With the purpose of preventing from shock wave as mentioned above, the flow fields in all domains are subsonic.…”
Section: Resultsmentioning
confidence: 99%
“…The heat transfer coefficient measurements for the GE-E3 first stage rotor blade tip with or without a groove were conducted in a fivebladed stationary linear cascade test rig [27][28][29][30], The results showed that the heat transfer coefficient distribution on the blade flat tip is significantly influenced by tip clearance height and inlet turbulence intensity. Shyam et al [33] presented that the unsteadiness in the tip clearance was mainly controlled by the inviscid high speed flow in a highly loaded transonic turbine. It is noted that the increase of the averaged heat transfer coefficient of the blade flat tip induced by the relative rotation of the casing is less than the reduction of that caused by the centrifugal force and Coriolis force.…”
Section: Introductionmentioning
confidence: 99%
“…Within the figure, color variations denote tip surface heat flux variations, and greyscale variations denote flow density gradient distributions which were employed in these studies utilized squealer configurations [57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72], partial squealer configurations [61,64,69], and winglet configurations [73,74]. Smooth blade tips were employed by Thorpe et al [75], Green et al [59], Key and Arts [62], O'Dowd et al [76,77], Wheeler et al [78], Zhang et al [55,56], Shyam et al [79], Atkins et al [80], Wheeler and Saleh [70], Anto et al [81], Virdi et al [68], Wheeler and Sandberg [82], Li et al [65], Zhang et al [83], Zhang and He [84], Wang et al [69], Zhou [71], Jung et al [61], Gao et al [85], and Kim et al [64]. Most of these investigations (which involved experimental measurements) employed annular or linear cascades with stationary blades.…”
Section: Interactions Which Included Thermal Transport and Convectivementioning
confidence: 99%
“…Most of these investigations (which involved experimental measurements) employed annular or linear cascades with stationary blades. Annular arrangements with rotating turbine blades were utilized by Dunn and Haldeman [58], Didier et al [86], Thorpe et al [75], Green et al [59], Key and Arts [62], Shyam et al [79], and Atkins et al [80].…”
Section: Interactions Which Included Thermal Transport and Convectivementioning
confidence: 99%
“…While relevant numerical and experimental studies have demonstrated the inherent aerothermal unsteadiness of high-speed leakage streams over flat tip geometries [2][3][4], the gap flow physics induced by alternative tip designs [5,6] is still scarcely documented in the open literature.…”
Section: Introductionmentioning
confidence: 99%